Artificial Intelligence in Language Education: A Review of Emerging Trends and Implications - Ain, Qurrat Ul; Azam, Mian Khurram Shahzad (Pakistan Languages and Humanities Review, 2025)
This research paper aims to investigate the impact of incorporating artificial intelligence in language education on students' and teachers’ educational achievements. Due to the swift advancements in Artificial Intelligence (AI) technology, AI is now being utilized in a variety of global sectors, including education. During this study, a systematic review method was used with PRISMA principles to identify 26 studies. The identified studies were analyzed using content and thematic qualitative analysis techniques. The findings revealed that to enhance an immersive learning experience among language learners, the integration of virtual reality and augmented technologies into language learning will be used to enhance language skills acquisition in an artificial intelligence-powered language learning environment. Additionally, for what aspects of language teaching will change in the context of AI-enabled tools or environments within the education industry, the research discovered that people's pronunciation of foreign language words, like EFL, will be altered by AI language learning tools. Policymakers, educational leaders, funders, and practitioners can use the information provided in this study to acquire a holistic understanding of current trends in the use of AI in EFL learning and teaching, whereas practical implications are provided to guide future AI use in EFL.